(3GdBKGQ GdEbJUGOjI hGdELJeGYjI dJWHjb efXheI GdNHR GdLOjOI ai eMGaXI Hfi Shja (B.s - (3YWhI, eMeO MSjf eMeO(B.s; (3QSJe, MSjf eMeO CMeO(B.s (2016)
(3jYJHQ GdNHR Gge echfGJ GdhLHI GdZPGFjI ai GdCSQI GdeUQjI dLejY GdeSJhjGJ GdeYjTjI ai Xd eMOhOjI GdONhd GdefNaVI hfXQG dchf QZja GdNHR jUfY HUaI GSGSjI ef GdbeM dGMJhGFI Ydi GdehGO GdfThjI hGdHQhJjfjI hGdajJGejfGJ GdJi JeO GdLSe HGMJjGLGJI ef GdSYQGJ GdMQGQjI GdJi JeKd fMh (B70% (3JbQjHG ceG JYO SdYI GdNHR gi GdGcKQ OYeG hGdJi jSJajO efgG eYXe aFGJ GdeLJeY Ydi GNJdGa ONhdge eY KHGJ SYQg efP SfhGJ WhjdI GdGeQ GdPi jMed GdOhdI eHGdZ WGFdI ai OYeg HdZJ bQGHI fMh (B11 (3edjGQ LfjI HfSHI JeKd fMh (B35,6% (3ef bjeI OYe GdehGO GdZPGFjI YGe (B2013/2014 .s
(3jMJhj Ydi eQGLY(B.s
(3edNU HGddZI GdCfLdjRjI(B.s
Keywords: x; (3GdNHRs -- (3LhGfH EbJUGOjIs